Metacognition: a strategic phenomenon for teaching and learning - Vélez Gutiérrez, Carlos Fernando (2021)
The discussion about metacognition, a recently characterized cognitive phenomenon, indispensable in education processes and problem-solving, falls within two particular fields of knowledge, i.e., evolutionary psychology and information processing. From these fields come the theoretical perspectives that emphasize phenomena such as the theory of the mind, the evolution of intelligence, the sense of knowledge, understanding, knowledge, and regulation. As conclusions, for the teacher, we emphasize the importance of raising awareness about students' mental processing manners as a possibility to adapt teaching strategies, an essential requirement to ensure that learning and development occur and that the student engages more effectively.